The Clinical and Psychological Condition of Elderly Patient Infected by Covid 19 with Comorbidity: Literature Review - Rahman, Ahmad Fadhlur; Kartinah, K (Proceeding ISETH (International Summit on Science, Technology, and Humanity), 2020)
Purpose: to know and describe the clinical and psychological condition of the elderly with Covid 19 with ComorbidityMethodology: This research is a literature review research by conducting a search using a nursing or health research data base, namely Google Schoolar, Science Direct, NCBI, and Elsevier with the keywords of each selected variable.Results: A total of 2340 patients were included in this literature review, with patient demographic characteristics including gender, age and comorbidities. A total of 1187 (51.1%) patients were male and 1153 (48.9%) were female, the age distribution of these patients was between 60-75 years (79%) and ≥75 years (21%) with comorbidities in the form of hypertension (45%), diabetes (24%), heart disease (19%), COPD (8%), kidney disease (4%), and liver disease (3 %). Clinical signs that appear in elderly people with hypertension and diabetes who are infected with Covid 19 are clinically found to be fever (33%), cough (26%), fatigue (13%), difficulty breathing (14%), anorexia (4%), diarrhea (4%), headache (2%), myalgia (2%), nausea (2%) and vomiting (1%). Psychologically, the signs and symptoms that appear in the elderly include depression, anxiety, and excessive feelings of fear.Applications / Originality / Value: The findings of clinical conditions that appear most in the literature review are fever, followed by cough, difficulty breathing, fatigue, anorexia, diarrhea, headache, myalgia, nausea and vomiting. While the psychological conditions that arise include stress, anger, depression, irritability, sleep disturbances, feelings of loneliness, excessive fear, and social disorders.